Pengaruh Media Virtual Reality Pembuatan Kompos Berbasis Joyful Learning terhadap Minat Belajar IPAS SD - Reynata Oktaviani; Surayanah Surayanah (FONDATIA, 2026)
Science learning positions products, processes, and scientific attitudes as an integrated whole, including strengthening students’ curiosity. However, science learning in elementary schools still often fails to optimally foster learning interest. This study aims to prove the effect of joyful learning-based virtual reality media for compost-making on elementary school students’ interest in learning Natural and Social Sciences (IPAS). This study used a quantitative approach with a quasi-experimental design. The research sample consisted of 27 students in the experimental class and 27 students in the control class, selected through random sampling. Data were collected using a learning interest questionnaire and analyzed using an independent samples t-test. The results show that the significance value of the independent samples t-test was 0.001, indicating a significant effect of using joyful learning-based virtual reality media on students’ learning interest in compost-making instruction. These findings affirm that learning interest is an important factor in learning because it can influence students’ engagement and cognitive achievement. The conclusion of this study shows that joyful learning-based virtual reality media is suitable for use as a more engaging science learning solution that supports the improvement of elementary school students’ learning interest.